IDENTIFIKASI PARASIT YANG MENGINFEKSI IKAN NILA (Oreochromis niloticus) PADA KOLAM BUDIDAYA DI DESA KUANHEUM - Immaria Fransira; Yudiana Jasmanindar; Asriati Djonu (Universitas Mataram, 2024)
Parasites are one of the main problems faced by fish farmers in Kupang district. The study aimed to identify parasites infecting tilapia (O. niloticus) in culture ponds in Kuanheum Village, Kupang Regency, East Nusa Tenggara. Tilapia (O. niloticus) were taken randomly and parasite identification observations were made at the Kupang Fish Quarantine, Quality Control and Fishery Product Safety Station Laboratory. The results were analyzed descriptively. The results of parasite identification showed that two types of parasites were found in tilapia (O. niloticus) in Kuanheum Village, namely Trichodina sp. and Cichlidogyrus sp.